Evaluation of antioxidants, pigments and secondary metabolites contents in Spirulina platensis - Ali, H.E.A. (Trans Tech Publications Ltd, 2014)
Spirulina platenisis was screened for antioxidant activity, water soluble pigments (phycobiliproteins) and secondary metabolites. Successive extraction by hexane, chloroform, ethyl acetate, ethanol (70) and water was carried out. Ethyl acetate extract demostrated high antioxidant activity with both 2,2´-diphenyl-1-picrylhydrazyl (DPPH) scavenging (47±0.32) and β- Carotene-linoleic acid bleaching assays (93.64±0.25),while, it showed very low antioxidant activity with 2, 2´-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical scavenging method. Relatively high phycobiliproteins (0.16±0.01 mg ml-1), total phenolic content (21.88±1.67 mg GAE g-1 dry wt.), total alkaloids (3.02±0.06) and total terpenoids (0.14±0.00) were determined. © 2014 Trans Tech Publications, Switzerland.